2000
DOI: 10.1034/j.1600-0560.2000.027005224.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term preservation of direct immunofluorescence staining in slides stored at room temperature

Abstract: To determine whether reproducible results from direct immunofluorescent tissue staining could be obtained after storing the slides at room temperature. We examined the original slides of 22 cases noted to be positive for direct immunofluorescence. Diagnoses include pemphigus, pemphigoid, lupus, dermatitis herpetiformis, lichen planus, and vasculitis. These specimens, initially evaluated during the period January 1997 to September 1998, were prepared with a standard immunofluorescence staining technique, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Various studies have been reported regarding the storage of DIF‐staining slides mounted with semipermanent mounting medium without losses of fluorescence 7,8,12,13 . Couser and Lewis 13 have proposed that kidney tissue slides may be stored for more than 2 years at 4°C, with no alteration in fluorescence intensity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various studies have been reported regarding the storage of DIF‐staining slides mounted with semipermanent mounting medium without losses of fluorescence 7,8,12,13 . Couser and Lewis 13 have proposed that kidney tissue slides may be stored for more than 2 years at 4°C, with no alteration in fluorescence intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Couser and Lewis 13 have proposed that kidney tissue slides may be stored for more than 2 years at 4°C, with no alteration in fluorescence intensity. Grimwood and Proffer 12 have used a ready‐to‐use permanent mounting medium and examined DIF‐positive slides from skin tissues of 22 patients over a period ranging from 6 to 30 months. They have reported that six slides could be stored for more than 18 months at room temperature with minimal loss of fluorescence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations